The Urgency of Indonesian Public Policy in Facing a War Situation in the Peace of Global Economic Competition - Rianto, Rianto; Prakoso, Lukman Yudho; Alman, Fariel Zulfikar; Soemantri, Asep Iwa; Patmi, Sri; Bermana, Seftiandra; Habibie, Sri Yaumil; Al-Mujaddid, Toriq Furqon (Indonesian Journal of Interdisciplinary Research in Science and Technology, 2024)
This article discusses the urgency of Indonesian public policy in facing the situation of "war in peace" amidst global economic competition. Competition between countries now includes economics, technology, and politics. Indonesia must adopt adaptive and proactive policies to maintain stability and advance national interests. Through qualitative analysis, this article explores strategies such as strengthening economic infrastructure, economic diversification, human resource development, economic diplomacy, and bureaucratic reform. National security policy must also include economic, cyber, and energy aspects. This research provides insights for policymakers, academics, and practitioners in formulating effective strategies to face the challenges of globalization.